Uncle Tom II : an American odyssey [videorecording (DVD)] - Malone, Justin; Jackson, Chad O.; Jackson, Chad O.; Ansell, Ryder; Elder, Larry; Elder, Larry; Criswell, Damon; Baucham, Voddie T., Jr., 1969-; West, Allen, 1961-; Tatum, Brandon; Carson, Ben; Swain, Carol M. (Carol Miller); et al. (UT Film, LLC., 2022)
"[This film] is an odyssey depicting the gradual demoralization of America through Marxist infiltration of its institutions. The film explores how this deceptive ideology has torn apart the fabric of society while using black America as its number one tool for its destruction. From Executive Producer Larry Elder and Director Justin Malone comes the continuation of their ... film, Uncle Tom (2020)"--Container insert.